Dataset of clinical laboratory tests according to ordering variance among family physicians in Calgary, Alberta, Canada - Leonard T. Nguyen (Data in Brief, 2019)
This data incorporates 2016 testing volumes ordered by family physicians and performed at Calgary Laboratory Services (CLS), the sole supplier of clinical laboratory services for the catchment area of the City of Calgary, Alberta, Canada. For each test, the mean number of tests ordered per patient was calculated over ordering Calgary physicians, along with arithmetic coefficients of variation (CV's). The latter parameter is reflective of variance in ordering practice among family physicians practicing in Calgary and is proposed as a benchmark measure for laboratory utilization in our accompanying research article [1]. The data table encompasses 358 tests ordered by at least 3 family physicians at a minimum total frequency of 100 within the 2016 study period and is presented in ascending order of rank in CV. Keywords: Clinical laboratory tests, Utilization, Variance, Laboratory medicine, Family medicine